Complications in patients with transfusion dependent thalassemia: A descriptive cross‐sectional study - Mohammad Faranoush; Pooya Faranoush; Iraj Heydari; Mohammad Reza Foroughi‐Gilvaee; Azita Azarkeivan; Ali Parsai Kia; Negin Sadighnia; Ali Elahinia; Afsoon Zandi; Mohammad Reza Rezvany; Nahid Hashemi‐Madani; Amir Ziaee; et al. (Health Science Reports, 2023)
Abstract Background and Aims One of the most common hemoglobinopathies globally related to blood transfusion and iron overload in the body is thalassemia syndrome. Increasing ferritin levels can cause severe damage to the patient's body organs. This study aims to evaluate the complications of iron overload on vital body organs in patients with transfusion‐dependent beta‐thalassemia. Methods This descriptive cross‐sectional study was performed in Iran University of Medical Sciences Hospitals on patients with a beta‐thalassemia major with frequent blood transfusions. To evaluate the effect of iron overload on vital body organs, hematologic and blood analysis, echocardiography with measurement of pulmonary artery pressure (PAP) and ejection fraction (EF) tests, bone densitometry, and audiometric tests were performed for all patients. Results Of the 1010 patients participating in this study, 497 (49%) were males, 513 were (51%) females aged 5–74 years, and the majority of participants (85%) were over 20 years old. This study demonstrated that increasing ferritin levels had no notable correlation with sex, cholesterol, low‐density lipoprotein, parathyroid hormone, T4, and aspartate aminotransferase. However, elevating ferritin levels had significant correlations with increasing triglyceride, phosphorus, thyroid stimulating hormone, alkaline phosphatase, alanine transaminase, and PAP levels, age, hearing disorders, splenectomy, osteoporosis, and decreasing high‐density lipoprotein, body mass index, calcium, and EF levels. Conclusion Improvement in beta‐thalassemia patients' survival and quality of life can be due to multidisciplinary care in a comprehensive unit through regular follow‐up and early complication detection.